Evaluation of the Use of an Electronic Prescription System Using the HOT-Fit Approach at the Pharmacy Installation of UNS Hospital Surakarta - Rio Adwika Pratama; Lucia Vita Inandha Dewi; Samuel Budi Harsono (MEDFARM: Jurnal Farmasi dan Kesehatan, 2025)
The e-Prescribing system has become an essential part of the digitalization of healthcare services aimed at improving accuracy, efficiency, and patient safety. Despite being adopted in many hospitals, the implementation of this system in Indonesia still faces challenges, including limited user understanding, uneven organizational support, and limited technological infrastructure. This study aims to evaluate the implementation of the e-Prescribing system at the Pharmacy Installation of UNS Hospital Surakarta using the HOT-FIT model, which assesses the Human, Organization, and Technology dimensions, as well as the Fishbone diagram to identify the root causes of the challenges faced. A mixed-methods approach was used, with quantitative data collected through questionnaires distributed to 30 pharmacy staff, analyzed using descriptive statistics, Pearson validity tests, and Cronbach’s Alpha reliability tests. The results showed that all questionnaire items were valid, with Pearson correlation values ranging from 0.518 to 0.898 and Cronbach’s Alpha of 0.918, indicating a very high level of internal consistency. The Human Fit dimension had a mean score of 4.2 (SD 0.5), Organization Fit 4.3 (SD 0.4), Technology Fit 4.5 (SD 0.3), and Net Benefit 4.6 (SD 0.2), indicating a positive impact on efficiency and user satisfaction. However, challenges related to inadequate training, slow system access, and limited integration with other systems remain. Fishbone analysis identified six key factors affecting system performance. The study concludes that while the e-Prescribing system shows positive results, improvements in training, infrastructure, and system integration are needed to enhance its effectiveness.